2014
DOI: 10.1159/000363734
|View full text |Cite
|
Sign up to set email alerts
|

Brief Tests such as the Clock Drawing Test or Cognistat Can Be Useful Predictors of Conversion from MCI to Dementia in the Clinical Assessment of Outpatients

Abstract: Background: The identification of patients with mild cognitive impairment (MCI) who are at high risk of conversion to dementia is a challenging clinical task. Aims: To investigate whether simple cognitive screening tests can predict the conversion from MCI to dementia and to study the impact of different patient characteristics on the progression rate. Methods: A retrospective, longitudinal study of 90 outpatients diagnosed with MCI at a psychogeriatric clinic in Norway was conducted. Baseline scores on the Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Comparisons between AD patients versus healthy controls found that a combination of reduced performance on the CDT and the MMSE were best in differentiating both MCI and AD patients from controls. In a retrospective, longitudinal analysis of patients with MCI who converted to dementia, Nesst et al [30] examined performance on the MMSE, CDT, and Neurobehavioral Cognitive Status Examination (Cognistat). These researchers found that in using these three tests, the combination of impaired CDT and Cognistat test performance was best in predicting conversion to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between AD patients versus healthy controls found that a combination of reduced performance on the CDT and the MMSE were best in differentiating both MCI and AD patients from controls. In a retrospective, longitudinal analysis of patients with MCI who converted to dementia, Nesst et al [30] examined performance on the MMSE, CDT, and Neurobehavioral Cognitive Status Examination (Cognistat). These researchers found that in using these three tests, the combination of impaired CDT and Cognistat test performance was best in predicting conversion to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Inability to make any reasonable representation of a clock is given a zero score [ 32 ]. These measures have been translated and adapted to Norwegian conditions [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In line with this study, our study revealed that a higher TBR < 3.9 was correlated with worse performance on TMTA, CDT and cued recall scores. Recent studies con rmed that compared with other neuropsychological tests, cued recall and CDT were thought to be more sensitive in identifying mild cognitive impairment and preferably valuable in predicting conversion from mild cognitive impairment to Alzheimer's disease [10,15]. Therefore, TBR < 3.9 was associated with cognitive impairment (memory dysfunction, de cits in visuospatial ability, and impaired executive functioning).…”
Section: Discussionmentioning
confidence: 99%